GLYCERIN AND POTASSIUM ON SOIL MICROBIAL ACTIVITY AND NUTRITION AND PRODUCTION OF BEET (Beta vulgaris) - Diaz-Medina, Alejandro; Mello-Prado, Renato de [UNESP]; Silva-Campos, Cid N. [UNESP]; Castellanos-Gonzales, Leonides; Cid-Rigobelo, Everlon [UNESP]; Suarez-Perez, Claribel; Barbosa-da Silva-Junior, Gabriel (Colegio Postgraduados, 2016)
The glycerin by-product of the production of biofuels (biodiesel) has possibility of agricultural use, but the scientific information is restricted. The objective of this study was to assess the effect of glycerin rates in the absence and presence of potassium fertilization on soil microbial activity, nutrition and production of beet (Beta vulgaris). The experiment was carried out in a greenhouse at Universidade Estadual Paulista, Jaboticabal, Brazil, using beet cv. Early Wonder, grown in pots with samples of Alfisol. The experimental design was randomized block, treatments were 0, 50, 100, 200 and 400 m(3) ha(-1) of glycerin, in the absence and presence of potassium (150 mg dm(-3)), with four replicates. Electrical conductivity, respiratory activity, microbial biomass, and available K were evaluated in the soil. Plant height, number of leaves, dry mass of the aerial portion and tubers were evaluated t. Glycerin at 16 and 90 m3 ha(-1) rates in absence and presence of K fertilization increased the production of beet plants dry matter, but induced salinity at higher rates and promoted reduction in K absorption and the soil microbial activity.
Keywords: Root crops; byproduct of biodiesel; potassium fertilization; soil salinity